Egyptian victories: the Praefectus Aegypti and the presentation of military success in the age of Augustus - Havener, Wolfgang (The alternative Augustan age, 2019)
The first princeps placed the newly conquered province of Egypt not under a senatorial governor but an equestrian prefect. This constituted a precedent in various respects. Being a new form of provincial administration, the prefecture offered its holders ample opportunity to distinguish themselves, not least in the field of military glory. This chapter addresses the questions of how the first praefecti, C. Cornelius Gallus, L. Aelius Gallus, and P. Petronius, exploited these opportunities and how their efforts were perceived by the princeps and the members of the senatorial elite. The praefectura provides an excellent case study to analyze the mechanisms underlying the development of a new elite in the Augustan era, as well as the ambitions and limitations of its individual members.
Gesehen am 22.07.2020